2020
DOI: 10.1051/e3sconf/202016901022
|View full text |Cite
|
Sign up to set email alerts
|

Study of cyantraniliprole sorption in soils of Russia

Abstract: The sorption of the new insecticide cyantraniliprole was studied by the batch equilibrium method. The study of quantitative characteristics of cyantraniliprole sorption by the soils of different types showed that this process is well described by linear isotherms. According to obtained values of Koc, cyantraniliprole belongs to medium-mobility active substances of pesticides. The sorption value of cyantraniliprole was closely correlated with the content of organic carbon and clay. The regression equation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The standardized regression coefficient with an order of OM (0.73) > clay (0.47) > CEC (0.24) indicated that OM was the main factor affecting the adsorption of cyantraniliprole, followed by clay and CEC. Similarly, Kolupaeva et al also found that K f was closely correlated with the content of organic carbon and clay …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The standardized regression coefficient with an order of OM (0.73) > clay (0.47) > CEC (0.24) indicated that OM was the main factor affecting the adsorption of cyantraniliprole, followed by clay and CEC. Similarly, Kolupaeva et al also found that K f was closely correlated with the content of organic carbon and clay …”
Section: Resultsmentioning
confidence: 75%
“…Similarly, Kolupaeva et al also found that K f was closely correlated with the content of organic carbon and clay. 40 Uptake and Accumulation of Cyantraniliprole by Wheat from Soils. Figure 5A shows the uptake and accumulation of cyantraniliprole by wheat in different soils.…”
mentioning
confidence: 99%